What should we know about dementia in the 21st century? A Delphi consensus study - Annear, M.; Toye, Christine; McInerney, F.; Eccleston, C.; Tranter, B.; Elliott, K.; Robinson, A. (BioMed Central Ltd., 2015)
Background: Escalating numbers of people are experiencing dementia in many countries. With increasing consumer needs, there is anticipated growth in the numbers of people providing diagnostic evaluations, treatments, and care. Ensuring a consistent and contemporary understanding of dementia across all of these groups has become a critical issue. This study aimed to reach consensus among dementia experts from English speaking countries regarding essential and contemporary knowledge about dementia. Methods: An online Delphi study was conducted to examine expert opinion concerning dementia knowledge with three rounds of data collection. A sample of dementia experts was selected by a panel of Australian experts, including a geriatrician and three professors of aged care. Purposive selection was initially undertaken with the sample expanded through snowballing. Dementia experts (N = 19) included geriatricians, psychologists, psychiatrists, neuroscientists, dementia advocates, and nurse academics from the United Kingdom, United States, and Australia. In the first round, these participants provided open-ended responses to questions determining what comprised essential knowledge about dementia. In the second round, responses were summarised into 66 discrete statements that participants rated on the basis of importance. In the third round, a rank-ordered list of the 66 statements and a group median were provided and participants rated the statements again. The degree of consensus regarding importance ratings was determined by assessing median, interquartile range, and proportion of experts scoring above predetermined thresholds. Correlation scores were calculated for each statement after the final round to identify changes in statement scores. Results: The Delphi experts identified 36 statements about dementia that they considered essential to understanding the condition. Statements about care for a person experiencing dementia and their care giver represented the largest response category. Other statements, for which full or very high consensus was reached, related to dementia characteristics, symptoms and progression, diagnosis and assessment, and treatment and prevention. Conclusions: These results summarise knowledge of dementia that is considered essential across expert representatives of key stakeholder groups from three countries. This information has implications for the delivery of care to people with the condition and the development of dementia education programs.